Analysis of heat-induced protein aggregation in human mitochondria - Wilkening, Anne (J Biol Chem, 2018)
Proteins in mammalian cells exhibit optimal stability at physiological temperatures, and even small temperature variations may cause unfolding and nonspecific aggregation. Because this process leads to a loss of function of the affected polypeptides and to cytotoxic stress, formation of protein aggregates has been recognized as a major pathogenic factor in human diseases. In this study, we determined the impact of physiological heat stress on mitochondria isolated from HeLa cells. We found that the heat-stressed mitochondria had lower membrane potential and ATP level and exhibited a decreased production of reactive oxygen species. An analysis of the mitochondrial proteome by 2D PAGE showed that the overall solubility of endogenous proteins was only marginally affected by elevated temperatures. However, a small subset of polypeptides exhibited an high sensitivity to heat stress. The mitochondrial translation elongation factor Tu (Tufm), a protein essential for organellar protein biosynthesis, was highly aggregation-prone and lost its solubility already under mild heat-stress conditions. Moreover, mitochondrial translation and the import of cytosolic proteins were defective in the heat-stressed mitochondria. Both types of nascent polypeptides, produced by translation or imported into the mitochondria, exhibited a strong tendency to aggregate in the heat-exposed mitochondria. We propose that a fast and specific inactivation of elongation factors may prevent the accumulation of misfolded nascent polypeptides and may thereby attenuate proteotoxicity under heat stress.